If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + 8k + 9 + -5k = 0 Reorder the terms: 3 + 9 + 8k + -5k = 0 Combine like terms: 3 + 9 = 12 12 + 8k + -5k = 0 Combine like terms: 8k + -5k = 3k 12 + 3k = 0 Solving 12 + 3k = 0 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 3k = 0 + -12 Combine like terms: 12 + -12 = 0 0 + 3k = 0 + -12 3k = 0 + -12 Combine like terms: 0 + -12 = -12 3k = -12 Divide each side by '3'. k = -4 Simplifying k = -4
| 2x^2+3x+7=2x^2+3x-5 | | (2x-23)=(x+3) | | 2.5k=-8 | | 2x^2+x-15/20-3x-2x^2 | | (s-5)(2s+7)= | | 2356/3=2c | | f(x)=x^2+8x+8 | | 2356/3=2 | | (8x+8)+(12x+2)=90 | | 3x-8=3x+12 | | 3y+9=5y-9 | | 6/k+4/3k=-2 | | 20y^2-5y=0 | | -3n^2+4n-59=-4n^2 | | 2w+2(4w-3)=114 | | (12x-51)=(6x+27) | | (b+5)(b-7)=(b-5)(b+7) | | 29u^2+48u-20= | | X^2+225/4=-15x | | (3x+54)=(8x+9) | | 49=3x-17 | | x^2+10xy-39y^2=0 | | 19=21-r | | 5x-4+3(x-2)=6 | | X(5x+3)=5x^2+3x-7 | | (-4m^2+3m-1)-(m+2)= | | 3e^2+20e-32= | | x^2-5xy-24y^2=0 | | 8x^3+40x^2=48x | | 3(x-4)+6(6x-2)-6=18 | | f(x)=6x-x^2-10 | | 5s^2-18s+16= |